Youtube Content as Fiduciary Guarantee In Banking - Fia Melinita (Inovasi Pratama Internasional. Ltd, 2027)
This research examines the implementation of copyright over YouTube content as an object of fiduciary security in Indonesian banking. YouTube content has economic value and can conceptually serve as an object of fiduciary security under Law No. 28 of 2014 on Copyright and Law No. 42 of 1999 on Fiduciary Security. Using a descriptive-analytical method, this research finds that its implementation has not run optimally due to obstacles in ownership and the transfer of rights, given that YouTube accounts are subject to Google's policies, which do not allow full transferability. Nevertheless, its juridical and economic potential remains substantial, so regulatory reform and a digital registration system are needed so that YouTube content can be legally recognized as an object of fiduciary security in Indonesia's banking sector.